1979
DOI: 10.3758/bf03206109
|View full text |Cite
|
Sign up to set email alerts
|

Word and nonword superiority effects in a letter detection task

Abstract: Subjects searched for predesignated consonant-letters embedded in strings of consonants, consonants and vowels, or consonants and numbers. In Experiments 1-3, detection was quicker in the consonant-vowel and consonant-number strings than in the consonant strings. Apparently, vowels and numbers were less confusable distractors than are nontarget consonants. Experiment 4 tested whether psychophysical or categorical information about letters and numbers enabled subjects to process consonant-vowel and consonant-nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1980
1980
1990
1990

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…White (1977) controlled for the physical factor by printing each of the six elements in a display in a different typeface or type size, and he obtained no category effect. Staller and Lappin (1979) found that search for consonant targets was just as fast through all-consonant strings as through consonant-vowel strings when the two distractor sets were equated on physical features. Krueger and Hettinger (in press) found no category effect for odd vs. even digits, presumably because the two sets share similar physical features (Levine, 1977).…”
Section: Subjectsmentioning
confidence: 98%
“…White (1977) controlled for the physical factor by printing each of the six elements in a display in a different typeface or type size, and he obtained no category effect. Staller and Lappin (1979) found that search for consonant targets was just as fast through all-consonant strings as through consonant-vowel strings when the two distractor sets were equated on physical features. Krueger and Hettinger (in press) found no category effect for odd vs. even digits, presumably because the two sets share similar physical features (Levine, 1977).…”
Section: Subjectsmentioning
confidence: 98%
“…Experiment 2 tested for this, as well as for a distinction between early (A to J) and late (Q to Z) letters. Other subsets of numbers and letters, for example, vowels and consonants (Staller & Lappin, 1979), also may be highly distinctive. Experiment 2 also tested for the effect of background order, using regular, reverse, and random orders (see Table 1), but did not adjust the letter sequences to equalize bigram frequency.…”
Section: Methodsmentioning
confidence: 99%
“…were able to demonstrate a word superiority effect with target precuing by introducing uncertainty about the target's position in the stimulus array. But Staller and Lappin (1979) argued that the graphic similarity between target and context letters was not adequately controlled in Carr et a1. When graphic similarity was equated across words and nonwords, Staller and Lappin did not find a word superiority effect.…”
Section: Specifically Thompson and Massaro Found That Thementioning
confidence: 99%